Anti-pathogenic activities of Gracilaria changii (Xia et Abbott) and effects of its associated bacteria on growth promoting properties - Muthar, Nurul Izzati (2018)
Seaweed contains various bioactive compounds that contributed to the pharmaceutical and food industries which demand high seaweed production. Limitation of healthy seedstock might lead to the reduction of seaweed production and the study of seaweed-bacteria interaction could potential enhance the growth of the organism. The interest in bacterial populations living in association with seaweed has increased during recent decades. Bacteria associated with seaweed secrete various beneficial compounds which can act as defense mechanism and also regulate the morphogenesis of seaweed. Thus, a study on the beneficial interaction between seaweed and bacteria especially on the growth promoting properties is crucial. The aim of this study was to determine the anti-pathogenic activities of Gracilaria changii and the effects of its associated bacteria on the growth promoting properties. The first study was to investigate anti-quorum sensing (anti-QS) and anti-biofilm activities from G. changii extracts. The anti-QS activities were screened using disc diffusion assay with mutant Chromobacterium violacein (CV026) strain as a quorum sensing (QS) biosensor strain. It was observed that only G. changii crude extracts at 240,000 ppm significantly (P < 0.05) inhibited the QS activity. Using thin layer chromatography (TLC), three out of six G. changii compounds separation showed significant (P < 0.05) QS inhibition zones after subjected to overlay assay. The results also showed that G. changii extracts inhibited (P < 0.05) the biofilm of pathogenic strain Vibrio campbellii BB120 at the concentration of 1 ppm after 24 hours incubated with G. changii extracts. In the second study, associated bacteria isolated from G. changii with anti-QS and anti-bacterial activities were characterized. A total of 28 different bacteria were isolated from G. changii in which 23 strains were epiphytic bacteria and the remaining 5 strains were endophytic bacteria. There was no anti-QS activity observed from bacteria associated G. changii using both well plate and disc diffusion assays with CV026 as the biosensor. No anti-bacterial activity was also detected from all bacterial isolates towards the four tested pathogens; Vibrio campbellii (BB120), V. parahaemolyticus (ATCC17803), V. anguillarum (ATCC43313) and V. alginolyticus (ATCC17749). The third study was conducted to determine the interaction between G. changii and the associated bacteria for growth promoting activities. Out of all the 28 bacteria isolated from the seaweed, BP-SW/7 which was identified as Halomonas sp. significantly (P < 0.05) promoted the highest G. changii bud formation. The bacterial density of Halomonas sp. also significantly (P < 0.05) increased from 107 to 109 CFU/mL after 15 days of co-culture with G. changii fragments. Moreover, the highest (P < 0.05) plant growth promoting hormone indole-3-acetic acid (IAA) production was also observed from the bacterial isolates BP-SW/7, Halomonas sp. after three days incubations. The results of this study showed that there is a symbiotic relationship between seaweed and certain associated bacteria particularly for growth promotions of both the seaweed and associated bacteria. Furthermore, G. changii could be an interesting source for biologically active compounds that may be applied for disease therapy instead commercial antibiotics.